Zinc and phosphorus interaction in nutrient solution affecting lettuce growth and yield - Moreira, Marialva Alvarenga; Fontes, Paulo Cezar Rezende; Camargo, Maria Isabel de (Pesquisa Agropecuaria Brasileira, 2001)
The experiment was carried out to evaluate the effect of Zn and P levels in nutrient solution on Zn and P absorption and lettuce yield (Lactuca sativa L.). A randomized block experimental design in 3 x 3 factorial arrangement with three replications was used. The treatments were three Zn levels: low, normal and high, corresponding to 0.0, 1.5 and 6.0 mM L-1 and three P levels: low, normal and high, corresponding to 0.01, 1.5 and 6.0 mM L-1 as ZnSO4.7H2O and KH2PO4. Twenty six days after transplantation (DAT), the leaf area and leaf dry weight were not influenced by the treatments. At 52 DAT, the leaf area, the leaf number and the shoot dry weight were not affected by Zn addition when the P level was low; but when P levels were normal and high, the normal and high Zn levels lead to the highest leaf area, leaf number, and shoot dry weight. Phosphorus concentrations in the marketable leaves at each Zn level were similar at P normal and high addition levels. The highest P concentration was observed in the stem followed by roots and marketable leaves. Zinc concentrations in the marketable leaves, stem and roots, increased with Zn addition to the nutrient solution.